A risk management perspective on CSR and the marginal cost of debt: empirical evidence from Europe - Othar Kordsachia (Review of Managerial Science, 2020)
This article investigates the association between CSR and marginal credit costs of European companies. We provide instance for a negative association based on a variety of model specifications and fine-grained measures for CSR. These results can be explained in light of the increasing relevance of socially responsible investors for financing costs of companies. We further apply the risk management perspective on CSR to the~credit market and show that the insurance-like property of CSR is especially relevant for companies in relative financial distress as measured by the interest coverage ratio. This study also examines the association between CSR assurance and credit costs and provides evidence that creditors reward non-financial insurance by reduced required rate of returns. Finally, we contribute to the corporate governance literature by modelling the association between different board characteristics and credit costs.
Keywords: M14; G30; 650; Cost of debt; Corporate social responsibility; Corporate governance; Risk mitigation